Expecting to die ebook - Jackson, Lisa (Alvarez & Pescoli, 2017)
In this thriller by the #1 New York Times bestselling author, mischievous teenagers are met by a twisted serial killer deep in the Montana woods. The menacing woods of Grizzly Falls, Montana, are not for the faint of heart. But for local teenagers, they're the perfect setting for partying and pranks. They don't know that lately there's a rapt audience amid the tangled trees, a killer with a different kind of game in mind. At the right moment, with the right victim, the deadly play begins. Detective Regan Pescoli is counting the days until her maternity leave. Exhausted and emotional, the last thing she needs is another difficult case—let alone a suspected serial killer. When a reality show arrives in town, and Regan's teenage daughter gets swept up in the media storm, she and her partner, Selena Alvarez, must somehow distinguish between rumor and truth. As more victims are found, and the nightmare begins to strike closer to home, Pescoli races to find the terror lingering in the darkness, where there are too many places to hide—and countless places to die... YOU DON'T WANT TO KNOW "Lisa Jackson shows yet again why she is one of the best at romantic suspense. A pure nail biter." —Harlan Coben, # 1 New York Times bestselling author DEVIOUS "Terrifying...a creepy thriller sure to please Jackson's many fans." — Publishers Weekly WITHOUT MERCY "Her latest whodunit hits all the marks, taking readers on a nail-biting roller-coaster ride." —Library Journal MALICE "Taut, twisty... Malic e displays the skilled Jackson at her best yet." —The Providence Journal